2020
DOI: 10.1186/s12870-020-02649-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of compound material alleviates saline and alkaline stress in cotton leaves through regulation of the transcriptome

Abstract: Background Soil salinization and alkalinization are the main factors that affect the agricultural productivity. Evaluating the persistence of the compound material applied in field soils is an important part of the regulation of the responses of cotton to saline and alkaline stresses. Result To determine the molecular effects of compound material on the cotton’s responses to saline stress and alkaline stress, cotton was planted in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Huili Zhang 1,2 †, Feifei Yu 1,3 †*, Peng Xie 1 †, Shengyuan Sun 4,5 †, Xinhua Qiao 6 †, Sanyuan Tang 1 , Chengxuan Chen 1 , Sen Yang 1,7 , Cuo Mei 1,7 , Dekai Yang 1,7 , Yaorong Wu 1 , Ran Xia 1 , Xu Li 4 , Jun Lu 4 , Yuxi Liu 4 , Xiaowei Xie 2 , Dongmei Ma 2 , Xing Xu 2 , Zhengwei Liang 8 , Zhonghui Feng 7,8 , Xiahe Huang 1 , Hong Yu 1 , Guifu Liu 1 , Yingchun Wang 1,7 , Jiayang Li 1,7 , Qifa Zhang 4 , Chang Chen 6,7 , Yidan Ouyang 4 *, Qi Xie 1,7,9 * The use of alkaline salt lands for crop production is hindered by a scarcity of knowledge and breeding efforts for plant alkaline tolerance. Through genome association analysis of sorghum, a naturally high-alkaline-tolerant crop, we detected a major locus, Alkaline Tolerance 1 (AT1), specifically related to alkaline-salinity sensitivity.…”
Section: A Gg Protein Regulates Alkaline Sensitivity In Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huili Zhang 1,2 †, Feifei Yu 1,3 †*, Peng Xie 1 †, Shengyuan Sun 4,5 †, Xinhua Qiao 6 †, Sanyuan Tang 1 , Chengxuan Chen 1 , Sen Yang 1,7 , Cuo Mei 1,7 , Dekai Yang 1,7 , Yaorong Wu 1 , Ran Xia 1 , Xu Li 4 , Jun Lu 4 , Yuxi Liu 4 , Xiaowei Xie 2 , Dongmei Ma 2 , Xing Xu 2 , Zhengwei Liang 8 , Zhonghui Feng 7,8 , Xiahe Huang 1 , Hong Yu 1 , Guifu Liu 1 , Yingchun Wang 1,7 , Jiayang Li 1,7 , Qifa Zhang 4 , Chang Chen 6,7 , Yidan Ouyang 4 *, Qi Xie 1,7,9 * The use of alkaline salt lands for crop production is hindered by a scarcity of knowledge and breeding efforts for plant alkaline tolerance. Through genome association analysis of sorghum, a naturally high-alkaline-tolerant crop, we detected a major locus, Alkaline Tolerance 1 (AT1), specifically related to alkaline-salinity sensitivity.…”
Section: A Gg Protein Regulates Alkaline Sensitivity In Cropsmentioning
confidence: 99%
“…High alkalinity boosts hydrogen peroxide (H 2 O 2 ) levels in cells and causes oxidative damage to cellular proteins, lipids, and DNA, which results in apoptosis ( 5 7 ). Aquaporins (AQPs) are conserved from prokaryotes to eukaryotes.…”
mentioning
confidence: 99%
“…PPM is an independently developed soil amendment with inorganic and organic polymers as the main components. It has high-water solubility, and can be applied through drip irrigation [ 15 ]. Studies have shown that polyacrylamide has no significant negative effects on aquatic ecosystems and soil organisms when used at recommended doses (10–20 kg·hm −2 ) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proper use of manganese sulfate avoids manganese deficiency and thus enhances plant growth and resistance, and generally the safe concentration of manganese sulphate solution is 0.1–1% [ 19 , 20 ]. Our previous study found that PPM had a variety of functional groups, such as carboxyl, alcohol hydroxyl, and silicone, whose main effect is to improve the soil structure and buffer saline ions in the soil [ 15 , 21 ]. The application of PPM could improve the resistance of cotton, wheat, and other crops to salt stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation